2001
DOI: 10.1177/0160449x0102600303
|View full text |Cite
|
Sign up to set email alerts
|

Free Riding: Trends in Collective Bargaining Coverage and Union Membership Levels in New Zealand

Abstract: Free riding occurs when non-union members receive the benefits of a union-negotiated collective bargain without contributing to the costs of achieving that bargain, whether by paying union mem bership dues or an agency fee. In New Zealand, free riding has been a significant difficulty for unions operating under the Employment Contracts Act 1991. Free riding had been approximately 16 per cent of collective bargaining coverage under previous employment laws. Free riding under the Employment Contracts Act represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…THE Elsewhere we have explored the impact of the lack of external legitimisation specifically on free-riding rates. Free-riding grew from around 16 per cent in 1989/90 under the system of industrial conciliation and arbitration, to 27 per cent in 1998/99 under the system of employment contracting (Harbridge & Wilkinson 2001). We concluded that, in the absence of a legislative system that allowed for coercion or 'cheap-riding', unions in industries with high labour turnover rates had limited effective responses to free-riding.…”
Section: Introductionmentioning
confidence: 87%
“…THE Elsewhere we have explored the impact of the lack of external legitimisation specifically on free-riding rates. Free-riding grew from around 16 per cent in 1989/90 under the system of industrial conciliation and arbitration, to 27 per cent in 1998/99 under the system of employment contracting (Harbridge & Wilkinson 2001). We concluded that, in the absence of a legislative system that allowed for coercion or 'cheap-riding', unions in industries with high labour turnover rates had limited effective responses to free-riding.…”
Section: Introductionmentioning
confidence: 87%
“…If anything, conventional (see, for example, Harbridge & Wilkinson, 2001) estimates of free riding are almost certainly too low. They only pertain to workers who are covered by collective agreements in organized workplaces.…”
Section: Freedom To Associate: Arguments For Compulsionmentioning
confidence: 99%
“…In Canada and the US, the legal duty of fair representation has also made union advocacy in contract administration and personal grievance cases a public good by obliging unions to defend the rights of both union and nonunion employees covered by the same collective agreement. Some union-negotiated provisions, such as a higher wage increase, may not be public goods in the usual sense, but nonunion employees may still benefit if employers extend such advantages more or less automatically to nonunion employees on individual contracts (Harbridge & Wilkinson, 2001). If union-negotiated terms and conditions are available to everyone (or extended to everyone by the employer), paying and non-paying employees alike, it generally makes no sense for a self-interested, utility-maximizing person to join a union and pay dues.…”
Section: Freedom To Associate: Arguments For Compulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the US, Chaison and Dhavale (1992, p. 355) conservatively estimate from the 1988 Current Population Survey that half of non-members covered by a collective agreement were free riders. With free riding more common in the service sector and among female and lower paid workers (Harbridge and Wilkinson, 2001), a feminization of the workforce together with structural shifts towards services could mean a further increase in free ridership. Moreover, unions face a dilemma: if they work hard and achieve much success in their collective bargaining, they create greater incentives for free-riding (Harbridge et al, 2002).…”
Section: Fairness and Social Justicementioning
confidence: 99%